2018
DOI: 10.1002/cmdc.201800118
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Optimization of Cytotoxic Lipidic Dialkynylcarbinols

Abstract: In line with a recent study of the pharmacological potential of bioinspired synthetic acetylenic lipids, after identification of the terminal dialkynylcarbinol (DAC) and butadiynyl alkynylcarbinol (BAC) moieties as functional antitumor pharmacophoric units, this work specifically addresses the issue of carbon backbone length. A systematic variation of the aliphatic chain length was thus carried out in both the DAC and BAC series. The critical impact of the length of the lipidic skeleton was first confirmed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…Systematic cytotoxicity assays against HCT116 cells showed that rac-20 and rac-20+1, with respective C 17 and C 18 carbon skeletons, are the most potent over the series. 65 These results are consistent with preliminary observations in the AAC series, where the shortening of the carbon skeleton from C 20 in the natural product 1 to C 17 in the artificial AAC 10 results in a five-fold increase in cytotoxicity (Table 1). 20 In the scalemic series, (R)-and (S)-20+1 were then prepared through the two-step method previously used for the synthesis of (R)-and (S)-20.…”
Section: Short Review Syn Thesissupporting
confidence: 91%
See 2 more Smart Citations
“…Systematic cytotoxicity assays against HCT116 cells showed that rac-20 and rac-20+1, with respective C 17 and C 18 carbon skeletons, are the most potent over the series. 65 These results are consistent with preliminary observations in the AAC series, where the shortening of the carbon skeleton from C 20 in the natural product 1 to C 17 in the artificial AAC 10 results in a five-fold increase in cytotoxicity (Table 1). 20 In the scalemic series, (R)-and (S)-20+1 were then prepared through the two-step method previously used for the synthesis of (R)-and (S)-20.…”
Section: Short Review Syn Thesissupporting
confidence: 91%
“…In the DAC racemic series, the length of the C 12 paraffinic chain of the reference rac-20 was increased up to C 16 in rac-20+4 and shortened down to C 9 in rac-20-3 (Scheme 17). 65…”
Section: Screening On the Lipidic Chain Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The IC50 value of a racemic LAC sample is thus expected to be roughly two times higher than that of the corresponding eutomer: results in the racemic series are however relevant prior to optimization . We reported that the acetylated analogue (S)-2 displayed a cytotoxicity in HCT116 similar to that of (S)-1, probably due to in cellulo hydrolysis of the acetate moiety, releasing the free DAC [5]. In contrast, the O-methylated derivative 3 proved to be inactive (IC50 > 10 µM) [6].…”
Section: Introductionmentioning
confidence: 94%
“…and (S)-3 (84% e.e. ), embedding two conjugated triple bonds in the lipidic chain [5]. A different approach was considered for the enantioselective synthesis of the simple LAC (S)-4 (> 99% e.e.).…”
Section: Introductionmentioning
confidence: 99%